Knowledge and practices associated with exposure to the taeniasis / cysticercosis complex among backyard pig breeders in the province of Jauja, Peru - Puerta, Daniel (2020)
The aim of this study was to identify and systematize information about the knowledge and practices associated with exposure to the taeniasis/cysticercosis complex among backyard pig breeders in the endemic district of Masma, province of Jauja, Peru. An interview guide was designed, and its execution was coordinated with the local authority. Consent was requested for the recording of the interviews. In addition, information was collected on the environment of the breeder's house and the raising of the pigs. The expressions were consigned in categories for the qualitative analysis: breeding habits, sanitary management, consumption of pork, economic importance of breeding, practices associated with exposure to the taeniasis/cysticercosis complex, hygienic practices and conditions, knowledge regarding the form of transmission and treatment of cysticercosis, and zoonotic condition and impact in the area. The quantitative analysis summarized information on the environment and the raising of pigs. The study found deficiencies in knowledge and practices that favoured exposure to T. solium eggs. The reduction in practices that favoured the transmission and spread of taeniasis/cysticercosis was due to experiences of suffering the disease in previous years in relatives and animals. It is required to develop prevention and control programs for the taeniasis/cysticercosis complex due to the economic importance and health of people.